Serbia : Financial Sector Assessment - World Bank (World Bank, Washington, DC, 2013)
The Financial Sector Assessment Program (FSAP) update team found that the authorities have progressed in implementing the key recommendations from the initial assessment. The 2005 FSAP team revealed a number of vulnerabilities, including (i) high credit growth, largely financed by foreign banks, which resulted in rising nonperforming loans (NPLs), and (ii) poor management and low capital of several systematically important state-controlled banks. The Basel Core Principle on Banking Supervision (BCP) assessment identified a number of deficiencies in banking supervision. The update team found that the authorities took action to address the issues highlighted by the 2005 FSAP. In particular, they adopted prudential measures to slow credit growth, including higher risk weights for foreign currency loans to un-hedged borrowers, and exposure limits to households. Two systemic state-controlled banks were privatized. Finally, a new banking law was enacted that significantly strengthened supervision on consolidated basis and improved corporate governance and transparency.